Evaluation of hop test movement quality to enhance return to sport testing. A cross-sectional study - Weber, Melanie; Müller, Mirjam; Mathieu-Kälin, Moritz; Caminada, Sandro; Häberli, Marina; Baur, Heiner (Frontiers in Sports and Active Living, 2024)
Introduction: Return to Sport tests with functional hop tests are often used to decide when a person is ready to return to sport after an anterior cruciate ligament (ACL) injury. Poor movement quality, such as knee valgus, hip adduction and hip internal rotation is considered a risk factor for ACL injury. However, it is unclear whether existing tests adequately cover the aspect of movement quality. This study aims to investigate whether there is a relationship between the calculated limb symmetry index (LSI) of hop tests as an indication of performance and the total score of the "Quality First" assessment (movement quality). The second aim is to examine the reliability of the newly developed "Quality First" assessment for evaluating movement quality in hop tests. Methods: The cross-sectional study recruited 34 patients with an ACL reconstruction. The vertical hop, single-leg hop for distance, and side hop tests were performed and recorded. The video recordings were assessed using the "Quality First" assessment. The Spearman correlation coefficient was calculated using the LSI and the "Quality First" total score. Intraclass correlation coefficients (ICC) and standard error of measurements (SEM) were used to calculate intra- and interrater reliability. In addition, the minimal detectable change (MDC) was determined. Results: The correlation test between the LSI and the "Quality First" total score showed no correlation for all three jumps (r = -0.1-0.02 / p-value = 0.65 - 0.93). The interrater reliability of the "Quality First" assessment showed fair to good reliability (ICC2: 0.45–0.60), with SEM ranging from 1.46 to 1.73 and the MDC from 4.06 to 4.8. Intrarater reliability was good to excellent (ICC3: 0.73–0.85), with SEM values ranging from 0.89 to 1.09 and the MDC from 2.47 to 3.01. Conclusion: The quality of movement, measured with the “Quality First” assessment, indicated no correlation with the calculated LSI from jump performance, therefore movement quality should also be examined in Return to Sport tests. The "Quality First" assessment shows fair to good reliability when used by different raters. When used multiple times by the same rater, the assessment has good to excellent reliability.